2011
DOI: 10.4103/1463-1741.85502
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of wind turbine noise on health-related quality of life

Abstract: We report a cross-sectional study comparing the health-related quality of life (HRQOL) of individuals residing in the proximity of a wind farm to those residing in a demographically matched area sufficiently displaced from wind turbines. The study employed a nonequivalent comparison group posttest-only design. Self-administered questionnaires, which included the brief version of the World Health Organization quality of life scale, were delivered to residents in two adjacent areas in semirural New Zealand. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
94
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 15 publications
8
94
4
1
Order By: Relevance
“…This renders them more spatially dispersed and, therefore, in greater proximity to consumers than conventional power plants, increasing the salience of energy supply (Pasqualetti, 2000;Wüstenhagen et al, 2007). In fact, for residents who live close to them, wind turbines have been found to have unpleasant noise emissions (see, for example, Knopper and Ollson (2011) or Shepherd et al (2011)) and, most importantly, negative impacts on landscape aesthetics (see, for example, Devine-Wright (2005), Jobert et al (2007), or Wolsink (2007)). Moreover, they have been shown to have negative impacts on biodiversity (see, for example, Lehnert et al (2014)).…”
Section: Introductionmentioning
confidence: 99%
“…This renders them more spatially dispersed and, therefore, in greater proximity to consumers than conventional power plants, increasing the salience of energy supply (Pasqualetti, 2000;Wüstenhagen et al, 2007). In fact, for residents who live close to them, wind turbines have been found to have unpleasant noise emissions (see, for example, Knopper and Ollson (2011) or Shepherd et al (2011)) and, most importantly, negative impacts on landscape aesthetics (see, for example, Devine-Wright (2005), Jobert et al (2007), or Wolsink (2007)). Moreover, they have been shown to have negative impacts on biodiversity (see, for example, Lehnert et al (2014)).…”
Section: Introductionmentioning
confidence: 99%
“…1 Some people assert that the infrasound generated by the wind turbines has a negative effect on the health of nearby residents, to the point where it is claimed that some have abandoned their homes in order to get away from what they believe to be the cause of their ill health, although this is disputed. 2 The two main hypotheses in this study are a) that infrasound has a direct physiological effect or b) the effect is psychogenic in nature otherwise known as a nocebo effect.…”
Section: Introductionmentioning
confidence: 99%
“…Some commentators suggest negative attitudes toward IWTs may contribute to reported annoyance [102]. However, researchers have found that IWTs were initially welcomed into the communities for their perceived environmental [35] or economic [37] benefits. Krogh (2011) wrote.…”
Section: Blaming the Victimmentioning
confidence: 99%